(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate treatment outcomes and associated factors in patients with lumbar spondylosis at Dien Bien Phu City Medical Center in 2025. Subjects and Methods: A pre–post interventional study was conducted in 80 patients with lumbar spondylosis who received electroacupuncture, Qigong exercises, and acupressure massage from April to October 2025. Results: The mean age was 53.64 ± 13.1 years, and females accounted for 63.75%. After 14 days, the mean VAS pain score decreased markedly from 4.08 ± 0.79 to 0.92 ± 0.54. Lumbar range of motion, spinal mobility measured by Schober’s test, and daily functioning all improved significantly (p < 0.05). Good and fair outcomes were achieved in 72.5% and 22.5% of patients, respectively. Patients aged under 60 years had a higher rate of good outcomes than those aged 60 years or older (80.76% vs. 57.14%; p = 0.024). No significant differences were observed according to sex, occupation, circumstances of onset, or disease duration. Conclusion: After 14 days of treatment, pain, mobility, and daily functioning improved; all recorded adverse events were mild and self-limiting.